Differences in the labor market by gender and aggregate income - Miguel A. Mascarúa Lara (Banco de México, 2024)
What are the effects on the labor market and aggregate income of frictions that restrict women's labor decisions that impede labor participation and composition being equal between men and women? To answer this question, I develop an occupational general equilibrium model with heterogeneous agents facing gender-based restrictions in labor participation and job selection. Then, I include an endogenous distribution of the size of formal and informal establishments and workers to replicate the Mexican data. Finally, I use the ENOE to calibrate the model and estimate gender-based frictions in the labor market in states and regions of Mexico and their effect on aggregate income. According to the model, aggregate income could increase by 4.3% without women's restrictions to entrepreneurship and by 32.1% without restrictions to entry and entrepreneurship. In addition, the southern states would witness the largest increases.
Keywords: J16; J70; O17; O40; O10; O50; 330; Misallocation; female entrepreneurship; gender frictions; informality